2014
DOI: 10.4148/2378-5977.6896
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary fat source and feeding duration on pig growth performance, carcass composition, and fat quality (2014)

Abstract: A total of 160 finishing pigs (PIC 327 Ã-1050; initially 100.5 lb) were used in an 84-d experiment to evaluate the effects of dietary fat source and feeding duration on growth performance, carcass characteristics, and fat quality. Dietary treatments included a corn-soybean meal control diet with no added fat or a 3 Ã-3 factorial with main effects of fat source (4% tallow, 4% soybean oil, or a blend of 2% tallow and 2% soybean oil) and feeding duration (d 0 to 42, 42 to 84, or 0 to 84). One pig was identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Inconsistent with the previous studies [32,39,40], the results of the present study demonstrated that formulating growing-nishing pig diets with 3% SO tended to increase hot dressing percent and increased cold dressing percent. As heavier or fatter carcasses positively in uence dressing percent [41], our results were not expected, considering no treatment differences were observed on BW at slaughter, hot and cold carcass weights, loin eye area, and 10th-rib backfat.…”
Section: Discussionsupporting
confidence: 76%
“…Inconsistent with the previous studies [32,39,40], the results of the present study demonstrated that formulating growing-nishing pig diets with 3% SO tended to increase hot dressing percent and increased cold dressing percent. As heavier or fatter carcasses positively in uence dressing percent [41], our results were not expected, considering no treatment differences were observed on BW at slaughter, hot and cold carcass weights, loin eye area, and 10th-rib backfat.…”
Section: Discussionsupporting
confidence: 76%
“…The ANC contains ether extract (EE) that ranges from 344 to 498 g EE/kg DM (Mthiyane and Mhlanga, 2017, Malebana et al, 2018, Nkosi et al, 2019, which depends on the processing method for oil extraction (Malebana et al, 2018). The high fat content in ANC could provide su cient energy in diets and allow pigs to improve feed e ciency, daily gains and thus increase muscle accretion (De la Llata et al, 2001, Stephenson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%